THE ASSOCIATION BETWEEN THE PRESENCE OF TYPICAL PNEUMONIA FINDINGS AND THE NEED FOR OXYGEN AND ANTIVIRAL THERAPY DURING THE OMICRON VARIANT EPIDEMIC IN JAPAN - T. Kitazawa; S. Nakayama; A. Yamamoto; Y. Wakabayashi (International Journal of Infectious Diseases, 2023)
Intro: Since the Omicron variant of novel coronavirus infection became endemic, the number of cases presenting with pneumonia has decreased and the prognosis has improved. However, it is unclear whether the typical pneumonia affected the need for antiviral treatment and oxygenation and outcome in case of Omicron variants. In this study, we analyzed the association between the presence of typical pneumonia findings and treatment and oxygenation, and prognosis during the Omicron variant epidemic in Japan. Methods: We enrolled patients who was hospitalized from January 1, 2022 to February 7, 2022, and whose CT scans were taken. The certainty of typical pneumonia on CT at admission, was analyzed using the COVID-19 Pneumonia Image Analysis Program of the 3D Image Analysis System Volume Analyzer Synapse Vincent. Patient background, treatment, oxygenation, and outcome were extracted from the medical records. Findings: Fifty-seven patients were included in the study, with a median CT certainty score of 58, ranging from 9 to 99. There were 22 patients in the highscore group, 13 in the intermediate-score group, and 22 in the low-score group. For the high, intermediate, and low score group, the rate of antiviral treatment 86%, 72%, and 72%, respectively (p=0.53). The rate of supplemental oxygen was required in 64%, 55%, 23%, respectively (p=0.02). The mortalities were 5%, 18%, 5%, respectively(p=0.33). Conclusion: During the Omicron variant epidemic, typical pneumonia findings were associated with oxygen supplementation, but not with antiviral therapy or mortality.